The Effect of Media of Chemondro and Hybrid of Video Conference on Teaching Learning towards Students’ Self-efficacy and Students’ Achievement on the Subject of Solubility and Solubility Product - Nira Listyawati; Jaslin Ikhsan; Kristian Handoyo Sugiyarto; Antuni Wiyarsi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
This research was conducted to analyze the effect of using the media of chemondro and hybrid video conferences in the teaching-learning toward students’ self-efficacy and students’ achievement on the subject of solubility and solubility product. The instruments of this research are the questionnaire and solubility and solubility product test. Thus, the research was set as quasi-experiment research using post-test only and non-equivalent control group design. By purposive sampling technique, the samples from 6 classes composed of 2 public senior high schools were selected. The classes were divided into 2 of hybrid learning with video conference and chemondro game (A), 2 classes of hybrid learning with video conference (B), and 2 classes of chemondro game (C). The corresponding data were collected on the basis of a self-efficacy learning questionnaire and a multiple-choice posttest of students' achievement in the subject of solubility and solubility product. The data were then tested by Manova. The results show that there was a significant difference in students’ self-efficacy and students’ chemistry cognitive achievement among the three classes, A, B, and C.